Network-wide on-line travel time estimation with inconsistent data from multiple sensor systems under network uncertainty - Hu Shao; William H. K. Lam; Agachai Sumalee; Anthony Chen (My University, 2017)
This paper proposes a new modeling approach for network-wide on-line travel time estimation with inconsistent data from multiple sensor systems. It makes full use of both the available data from multiple sensor systems (on-line data) and historical data (off-line data). The first- and second-order statistical properties of the on-line data are investigated together with the data inconsistency issue to estimate network-wide travel times. The proposed model is formulated as a generalized least squares problem with non-linear constraints. A solution algorithm based on the penalty function method is adopted to solve the proposed model, whose application is illustrated by numerical examples using a local road network in Hong Kong.
Keywords: Line (geometry); Least-squares function approximation; Real-time data; Traffic Prediction and Management Techniques